Government Accounting Standards Compliance on Financial Reporting Quality in Regional Public Service Agencies - Yasifa, Nurisnaini; Muhsyaf, Saipul Arni (Universitas Trunojoyo Madura, 2025)
This study examines the effect of compliance with Government Regulation (PP) No. 71 0f 2010 on the financial reporting quality of Regional Public Service Agencies (BLUD) in health centers and hospitals in Bima Regency. The research employs a quantitative explanatory approach, using purposive sampling to survey 88 BLUD employees involved in financial reporting. We analyzed the data using simple linear regression via SPSS 23. Compliance with Government Regulation (PP) No. 71 of 2010 significantly positively influences financial reporting quality, explaining 63.9% of its variance. Transparency was identified as an aspect needing improvement. This study provides empirical evidence from an under-researched Eastern Indonesian context, bridging the gap between institutional theory and public sector accounting practices. It uniquely combines implementing accrual-based accounting reforms. BLUD should enhance transparency and conduct regular internal evaluations to ensure consistent compliance. Policymakers can use these findings to strengthen regulatory frameworks for public sector accountability. Future studies should incorporate additional variables like human resource competence and information technology to explain the remaining 36.1% variance in financial reporting quality.